Development of a personalized therapeutic strategy for ERBB-gene-mutated cancers. (8th January 2018) - Milewska, Malgorzata; Cremona, Mattia; Morgan, Clare; O'Shea, John; Carr, Aoife; Vellanki, Sri HariKrishna; Hopkins, Ann M.; Toomey, Sinead; Madden, Stephen F.; Hennessy, Bryan T.; Eustace, Alex J.
Background: The application of genomic technologies to patient tumor samples identified groups of signaling pathways which acquire activating mutations. Some cancers are dependent on these mutations and the aberrant proteins resulting from these mutations can be targeted by novel drugs which can eradicate the cancer. Methods: We usedwww.cbioportal.org to determine the frequency of ERBB mutations in solid tumors. We then determined the sensitivity of a panel of cell lines to clinically available PI3K inhibitors. Using proliferation and apoptosis assays as well as functional interrogation with reverse phase protein arrays we demonstrated the impact of targeting ERBB-mutant cancers with the combination of a PI3K inhibitor and the pan-HER family inhibitor afatinib. Results: In over 14, 000 patients we found that 12% of their tumors have an ERBB family gene mutation (EGFR, ERBB2, ERBB3 and ERBB4). In cancers not commonly associated with HER family protein overexpression, such as ovarian, endometrial, melanoma and head and neck cancers ( n = 2116), we found that ERBB family mutations are enriched, occurring at rates from 14% to 34% and commonly co-occur with PIK3CA mutations. Importantly, we demonstrate that ERBB family mutant cancers are sensitive to treatment with PI3K inhibitors. Finally we show that the combination of afatinib and copanlisib represents a novel therapeutic strategy for patients whose cancers harbor both ERBB family and PIK3CA mutation. Conclusions: We demonstrate that ERBB family mutations are common in cancers not associated with overexpression or amplification of HER family proteins. These ERBB family mutant cancers are sensitive to treatment with PI3K inhibitors, and when combined with pan-HER inhibitors have synergistic antiproliferative effects.